The Tyrolean Iceman and His Glacial Environment During the Holocene. Issue 2 (27th September 2016) - Kutschera, Walter; Patzelt, Gernot; Steier, Peter; Wild, Eva Maria
Abstract: This paper summarizes the present knowledge on the variation of summer temperatures in the European Alps throughout the Holocene by combining the results of an extraordinary archaeological find with the information gathered from glacier and tree-line movements. As it turns out, there were several distinct periods were the glaciers were smaller than today, allowing in some periods the growth of trees in areas, which even now are still covered with ice. On average, the first half of the Holocene was warmer than the second half, with temperatures starting to decrease around the time of the Iceman some 5000 yr ago. One of the coldest periods during the Holocene, the so-called Little Ice Age (LIA), lasted from about AD 1300 to 1850. It is well known that since then the Alpine glaciers have been receding, most likely amplified by anthropogenic impact. The study of temperature variations before human influence may help to eventually disentangle natural and anthropogenic causes for the global warming of our time.